(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
In the analytical article, the author reviews modern scientific studies of foreign and domestic authors devoted to the study of the pathogenesis of toxic liver lesions. The author analyzes the immuno-inflammatory mechanisms, oxidative stress, cytolytic breakdown of hepatocytes and neurointoxication processes, which are the basis of the pathogenesis of toxic liver lesions.